2005
DOI: 10.1246/bcsj.78.1757
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Reaction Rate Constants of Antioxidants with the Hydroxyl Radical by a Rapid-Flow ESR Method

Abstract: The reaction rate constants of antioxidants with the hydroxyl radical (HO•) were determined by a rapid-flow ESR method. ESR spectra of the antioxidant radical formed by a reaction with HO• generated from the Ti3+ + H2O2 system were measured. When an antioxidant and ethanol were mixed with HO•, a superposed spectrum of the 1-hydroxyethyl radical and antioxidant radical was obtained. The intensity ratio of the signals of these radicals was calculated from the doubly integrated curve, and then the ratio of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The relative activation energies obtained from their reaction rate constants and computed O-H bond dissociation energies shows that the Evans Polyani relationship is valid for the series albeit that there is a departure from the linear plot for the alcohols which suggested that their transition states were stabilised by a polar effect. 86 Previously, we had reported that relative rates for tocopherols and other sterically hindered phenols, in H-atom transfer reactions to oxygen centred radicals, correlated well with the computed free energies, obtained from calculations of both enthalpies and entropies for the O-H dissociation step. 87 The ''b-carotene'' dilemma refers to the seemingly unpredictable behaviour of the material, which while well demonstrated to be an efficient radical scavenger, when implemented as a dietary supplement in smokers, it caused an elevation in rates of lung cancer from the controls, with the result that the study was brought to a halt well ahead of its originally scheduled end.…”
Section: Radical-scavengingsupporting
confidence: 57%
“…The relative activation energies obtained from their reaction rate constants and computed O-H bond dissociation energies shows that the Evans Polyani relationship is valid for the series albeit that there is a departure from the linear plot for the alcohols which suggested that their transition states were stabilised by a polar effect. 86 Previously, we had reported that relative rates for tocopherols and other sterically hindered phenols, in H-atom transfer reactions to oxygen centred radicals, correlated well with the computed free energies, obtained from calculations of both enthalpies and entropies for the O-H dissociation step. 87 The ''b-carotene'' dilemma refers to the seemingly unpredictable behaviour of the material, which while well demonstrated to be an efficient radical scavenger, when implemented as a dietary supplement in smokers, it caused an elevation in rates of lung cancer from the controls, with the result that the study was brought to a halt well ahead of its originally scheduled end.…”
Section: Radical-scavengingsupporting
confidence: 57%
“…It is thought that the structures of the transition states for the alcohols are stabilised by a polar effect. 66 The O-H bond dissociation enthalpies (BDEs) of a series of thirteen oximes (R 2 CQNOH) have been reported. Experimental anchor points used to validate the results of theoretical calculations include: (1) the O-H BDEs of Bu t 2 CQNOH, Bu t Pr i CQNOH and Bu t (1-adamantyl)CQNOH (determined previously from the heat released in the reaction between Bu t 2 CQNO d and PhNHNHPh in benzene), all of which were decreased by 1.7 kcal mol À1 to reflect a revision to the heat of formation of (E)azobenzene (which, in fact, has significant implications for other BDEs) and to correct for the heat of hydrogen bonding of Bu t 2 CQNOH to benzene (0.43 kcal mol À1 ); (2) the measured rates of thermolysis of six R 2 CQNOCH 2 Ph derivatives at 423 or 443 K, which were used to derive O-H BDEs for the corresponding R 2 CQNOH molecules.…”
Section: Organic Radicalsmentioning
confidence: 99%